Rancang Bangun Pemilah Sampah Organic, Anorganik dan Metal Secara Otomatis Berbasis IoT - R, Marcellinus Dias; Santoso, Santoso; Hartayu, Ratna; Swarga, Lutfi Agung (Institut Teknologi Adhi Tama Surabaya, 2025)
The automatic waste sorting system based on Internet of Things (IoT) technology is designed to address the waste management issues in Indonesia. This system utilizes various sensors, such as capacitive sensors, inductive sensors, infrared sensors, and ultrasonic sensors, to detect and automatically separate organic, inorganic, and metal waste. The system also uses servo motors to open and close trash bins according to the detected waste type, along with an Arduino Mega 2560 with a Wi-Fi module to control and send notifications via the Telegram application. The testing results show that the system can sort waste with 95% accuracy, with organic waste usable as compost and inorganic and metal waste recyclable. It is expected that this system will improve waste management efficiency, creating a cleaner and more sustainable environment..